Trends, contradictions, and patterns of functioning of interregional and inter-municipal cooperation institutions - R. F. Gataullin; E. R. Chuvashaeva (Вестник университета, 2025)
The purpose of the study is to reveal the existing trends, contradictions, and patterns in functioning and development of interregional and inter-municipal cooperation institutions. Contradictions in the encountered institutions functioning have been highlighted in their powers and performance. Among the trends in the institutions development the following have been noted: management decentralization, strengthening of the regional and municipal authorities role in planning and implementation of spatial development projects, vector for strengthening sustainability, sustainable development principles integration in strategies and projects that allows to consider not only economic and environmental aspects in planning, but also social ones, strengthening of innovativeness and financing of interregional and inter-municipal cooperation institutions, spatial development management digitalization, public participation in solving problems of improving interregional and inter-municipal cooperation, and strengthening of international cooperation in relevant projects implementation. Among the patterns in the institutions development it is necessary to define their focus on functioning in the context of horizontal links globalization, growth of development sustainability and population mobility, digitalization and innovativeness, ensuring security on the basis of risk management, which implies legal integration and standards harmonization, intensive exchange of the best projects, activation of local authorities and population in projects implementation. The author’s proposals for improving institutions in modern conditions include transition to the project approach, reorientation of the policy in this area to ensure mutual benefit, and priority in supporting projects of inter-territorial importance, capable of ensuring territorial connectivity and unity of economic space.